2015
DOI: 10.3390/jcm4081536
|View full text |Cite
|
Sign up to set email alerts
|

Update of Endocrine Dysfunction following Pediatric Traumatic Brain Injury

Abstract: Traumatic brain injuries (TBI) are common occurrences in childhood, often resulting in long term, life altering consequences. Research into endocrine sequelae following injury has gained attention; however, there are few studies in children. This paper reviews the pathophysiology and current literature documenting risk for endocrine dysfunction in children suffering from TBI. Primary injury following TBI often results in disruption of the hypothalamic-pituitary-adrenal axis and antidiuretic hormone production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 76 publications
(172 reference statements)
3
38
0
2
Order By: Relevance
“…Our findings converge with prior studies emphasizing that neuroendocrine abnormalities are not strongly related to severity of TBI and may emerge during chronic stages of recovery (Reifschneider et al, 2015). There is a paucity of literature on long-term neuroendocrine changes after physical injury in youth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings converge with prior studies emphasizing that neuroendocrine abnormalities are not strongly related to severity of TBI and may emerge during chronic stages of recovery (Reifschneider et al, 2015). There is a paucity of literature on long-term neuroendocrine changes after physical injury in youth.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic exposure to adversity has the potential to alter the set-point or threshold of HPA activity and reactivity, resulting in either over- or underactivity (Yehuda et al, 2010). Although acute stress reactions may be adaptive, the cumulative effects of chronic activation of these environmentally sensitive systems contribute to poor physical and psychological health, including internalizing disorders (Lupien et al, 2009), immune dysfunction, hypertension, insulin resistance (McEwen, 1998; Pacella et al, 2013), and hypopitutitarism (Reifschneider et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The narrow pituitary stalk is vulnerable to direct damage by mechanical compression, shearing or vascular injury, or indirectly compromised by brain swelling (Dusick et al, 2012; Reifschneider et al, 2015). Haemorrhage, necrosis and fibrosis of the pituitary stalk, anterior and posterior pituitary have been reported upon autopsy after fatal TBI (Klose and Feldt-Rasmussen, 2015; Kornblum and Fisher, 1969; Tanriverdi and Kelestimur, 2015), and amongst survivors of adult TBI, pituitary atrophy is evident by MRI up to at least 11 months post-injury (Maiya et al, 2008).…”
Section: Moving Forward: Delineating Potential Biological Mechanismsmentioning
confidence: 99%
“…In recent years, numerous studies have identified hypopituitarism as a common consequence of TBI, although the reported incidence varies considerably depending upon assay methodology, diagnostic criteria, patient selection, and duration between injury and evaluation (Reifschneider et al, 2015; Richmond and Rogol, 2014). Growth hormone and gonadotropin deficiencies are the most common pituitary hormone abnormalities reported in TBI patients (Silva et al, 2015), however, any part of the hypothalamic-pituitary axis can be affected.…”
Section: Moving Forward: Delineating Potential Biological Mechanismsmentioning
confidence: 99%